DIFERENCIAS AUDITIVAS DEL TALLO CEREBRAL EN EL GALLO (GALLUS GALLUS) Y EL CUY (CAVIAS PORCELLUS). ESTUDIO ELECTROFISIOLOGICO COMPARATIVO DE LOS POTENCIALES PROVOCADOS AUDITIVOS TEMPRANOS - Morales Martínez, José De Jesús; Ayala Guerrero, Fructuoso; Luna, Adrían Poblano (Instituto de Ecología, A.C., 2002)
Hearing characteristics show gradual modifications through vertebrate evolution. These changes facilitate the communication through songs in birds. Likewise, the audition in mammals enabled more complex abilities, such as a true social speech and complex behavior. In the present work, a comparative analysis of auditory responses obtained from an avian species (Gallus gallus) and a mammalian one (Cavias porcellus)was carried out. Auditory responses were measured in both specimens with electrode needles placed in the head. Stimuli consisted of alternated clicks delivered in a sound-buffered chamber through a loud speaker placed at a distance of 70 cm in front of the head of the animal. The animals were anesthetized with ketamine hydrochloride (50 mg/kg). Results showed that the brainstem auditory evoked potentials (BAEP) are morphologically similar in the two species studied. Such potentials are characterized by presenting five waves with shorter latency in the mammalian model.